Planning a Maker activity: Dynamic, flexible planning to meet student needs - Ciocca, Jean-Luc; Cotnam-Kappel, Megan (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2022)
The article explores how teachers in francophone Ontarian schools conceptualize the planning of a Maker activity. Anchored in the do-it-yourself tradition, the unprecedented enthusiasm in education for this type of activity raises certain planning challenges and issues. The results of our qualitative analyses of interviews with two teachers (6th grade and 11th grade technical) underscore that teachers undertake three actions when planning a Maker activity: 1) create a Maker community spirit; 2) implement a Maker mentality through actions; and 3) adopt a planning-in-action approach. Our research underscores that a form of planning that we define as planning-in-action seems specific to Maker activities in a classroom at the primary or secondary level.